Growth, inequality, and poverty reduction in developing countries: Recent global evidence - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The study presents recent global evidence on the transformation of economic growth to poverty reduction in developing countries, with emphasis on the role of income inequality. The focus is on the period since the early/mid-1990s when growth in these countries as a group has been relatively strong, surpassing that of the advanced economies. Both regional and country-specific data are analysed for the US1.25 and US2.50 level poverty headcount ratios using the most recent World Bank data. The study finds that on average income growth has been the major driving force behind both the declines and increases in poverty. The study, however, documents substantial regional and country differences that are masked by this average dominant growth story. While in the majority of countries growth was the major factor behind falling or increasing poverty, inequality, nevertheless, played the crucial role in poverty behaviour in a large number of countries. And, even in those countries where growth has been the main driver of poverty reduction, further progress could have occurred under relatively favourable income distribution. For more efficient policy-making, therefore, idiosyncratic attributes of countries should be emphasized. In general, high initial levels of inequality limit the effectiveness of growth in reducing poverty while growing inequality reduces poverty directly for a given level of growth. It would seem judicious, therefore, to accord special attention to reducing inequality in certain countries where income distribution is especially unfavourable. Unfortunately, the present study also points to the limited effects of growth and inequality-reducing policies in low-income countries.
Keywords: O49; D31; I32; O11; 330; growth; inequality; poverty; developing countries; Wirtschaftswachstum; Armut; Einkommensverteilung; Entwicklungsländer